2010
DOI: 10.1007/s11269-010-9635-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Annual Rainfall in the Macta and Tafna Catchments, Northwestern Algeria

Abstract: We analyzed the temporal variability of annual precipitation measured at five stations in the Macta (14,380 km 2 ) and Tafna (4,949 km 2 ) catchments located in northwestern Algeria, in connection with climate indices over the 1950-2004 period. Analysis of the temporal variability using linear regression and Pettitt test revealed a significant decline in annual rainfall in the mid-1970s in both basins. Furthermore, a decrease of at least 20% of total annual rainfall is also observed at all five stations. As fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 56 publications
2
73
0
7
Order By: Relevance
“…Mais ni le test de Pettitt, ni le test de Mann-Kendall ne confirment l'existence d'une date de rupture ou une tendance significative sur cette période. Meddi et al (2010) La recherche de tendance nous a aussi amenés à analyser les précipitations saisonnières pour la même période. A ce niveau aussi, aucune tendance n'a pu être détectée pour les précipitations saisonnières.…”
Section: Discussion Et Conclusionunclassified
See 1 more Smart Citation
“…Mais ni le test de Pettitt, ni le test de Mann-Kendall ne confirment l'existence d'une date de rupture ou une tendance significative sur cette période. Meddi et al (2010) La recherche de tendance nous a aussi amenés à analyser les précipitations saisonnières pour la même période. A ce niveau aussi, aucune tendance n'a pu être détectée pour les précipitations saisonnières.…”
Section: Discussion Et Conclusionunclassified
“…L'irrégularité et l'hétérogénéité spatiale des régimes pluviométriques ont souvent été mises en avant comme étant la cause principale de la variation de l'écoulement dans le bassin de la Tafna. Dans une analyse de tendance sur des séries de pluies annuelles algériennes, Meddi et al (2010) …”
Section: Introductionunclassified
“…Par ailleurs, de nombreuses études ont montré que les variations du régime pluviométrique dans le bassin méditerra-néen sont liées à la circulation atmosphérique générale tels que: l'Oscillation Nord Atlantique NAO (Salameh, 2008;Xoplaki et al, 2004;Lopez and Frances, 2010;Brandimarte et al, 2011) El Nino South Oscillation (ENSO) (Meddi et al, 2010;Kiladis and Diaz 1989;Rodo et al, 1997;Van Oldenborgh et al, 2000;Lloyd-Hughes and Saunders, 2002;Knippertz et al, 2003), MO (Mediterranean oscillation) (Conte et al, 1989) et WeMO (West Mediterranean Oscilation) (Martín-Vide and Lopez-Bustins, 2006). En Algérie, l'étude menée par Meddi et al (2010) montre que la variabilité temporelle des précipitations annuelles de l'Ouest de l'Algérie est influencée par ENSO.…”
Section: Introductionunclassified
“…En Algérie, l'étude menée par Meddi et al (2010) montre que la variabilité temporelle des précipitations annuelles de l'Ouest de l'Algérie est influencée par ENSO.…”
Section: Introductionunclassified
“…According to the study carried out by in North West of Algeria at a large-scale, the results showed a generally downward trend in annual rainfall which is consistent with those obtained in present investigation. Indeed, several studies link the decline in precipitation to the Northern Atlantic Oscillation (NAO) which affected the variability of climate index and the hydro climatic variables (e.g., temperature, rainfall, streamflow) in the Mediterranean basin (Rodo et al, 1997), in North Africa (Brandimarte et al, 2011) and in North Algeria, especially of the western region (Meddi et al, 2010).…”
Section: Seasonal and Annual Trends In Rainfallmentioning
confidence: 99%